Model Faktor Determinan Pemilihan Karir Mahasiswa Akuntansi Sebagai Konsultan Pajak Pada Universitas Swasta Di Kota Medan - Nainggolan, Edisah Putra; Sari, Maya; Alpi, M. Firza; Jufrizen, Jufrizen (Jurnal Akuntansi dan Pajak, 2020)
This study aims to produce a Model of Determining Career Selection of Accounting Students as Tax Consultants at Private Universities in the City of Medan. While the specific objective: Studying the factors that influence the Career Selection of Accounting Students as a Tax Consultant at a Private University in the City of Medan. The population in this study were all accounting students in several private universities in Medan. Sampling in this study used purposive sampling with proposals from accounting majors in semester II, IV, VI and VIII. Determination of the number of samples in this study is based on the Central Limit Theorema which says the number of samples to reach a normal curve of at least 30 respondents. The type of data used in this study uses primary data. Data collected by distributing questionnaires to students. The data analysis technique used is descriptive statistical analysis and multiple regression analysis. The results showed that partial and simultaneous work environment, personality, social values, professional recognition, professional training and gender significantly influence the Career Interests of Private University Accounting Students in Medan City